(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
Cyber piracy is considered one of the modern crimes due to its close connection with the technological and digital developments currently witnessed worldwide, which have facilitated and accelerated the circulation of information and data. Cyber piracy constitutes an act of trespass and aggression against such information and data. Given its particular nature and seriousness, the Algerian legislator has sought to confront this crime by enacting a set of laws aimed at combating and limiting its spread.